Quality function deployment approach to measure supply chain performance: A case study on garments accessories industries - Ashrafuzzaman, Md.; Al-Maruf, A.; Mahbubul, I.M.; Malek, A.B.M.A.; Mukaddes, A.M.M. (Inderscience, 2016)
In the competitive markets, effective management of supply chain and realisation of customer expectations are crucial factors for the better performance of an organisation. In the modern era, performance measurement has a significant role to get the competitive advantage. Quality function deployment (QFD) methodology is the most reliable and proved method to identify customer-based strategy. The objective of this research is to determine critical customer requirements and prioritise them to determine the critical supply chain factors to improve supply chain performances. This is a case study on six-selected garments accessories industries (GAI) in Bangladesh with respect to 17 readymade garments industries and buying house as a customer. This paper shows a new system of supply chain performance evaluation using transformation matrix called quality function deployment. By this system, it is possible to measure supply chain performance of any kind of manufacturing industry. Research findings can be used for the selection of manufacturing industries supply chain strategy.